Association between phosphodiesterase 4D gene and ischaemic stroke. Issue 9 (16th August 2006) - Staton, J M; Sayer, M S; Hankey, G J; Attia, J; Thakkinstian, A; Yi, Q; Cole, V J; Baker, R; Eikelboom, J W
Abstract : Background: An association between the phosphodiesterase 4D ( PDE4D ) gene and risk of ischaemic stroke in an Icelandic population has been suggested by the deCODE group. Methods: A case–control study of 151 hospitalised patients with first-ever ischaemic stroke and 164 randomly selected age-matched and sex-matched community controls was conducted. PDE4D genotypes for the six single-nucleotide polymorphisms (SNPs) previously reported to be independently associated with stroke were determined, common haplotypes were inferred using the expectation-maximisation algorithm, and SNP and haplotype associations with stroke were examined. A meta-analysis of published studies examining the association between PDE4D and stroke was also carried out. Results: Our study of Australian patients with stroke showed an independent association between ischaemic stroke and PDE4D SNP 89 (CC: odds ratio (OR) 5.55, 95% confidence interval (CI) 1.02 to 30.19; CA: OR 1.68, 95% CI 0.96 to 2.96; AA: OR 1 (reference)), SNP 87 (CC: OR 2.13, 95% CI 1.08 to 4.20; TC: OR 1.64, 95% CI 0.89 to 3.00; TT: OR 1 (reference)) and SNP 83 (TT: OR 2.16, 95% CI 1.08 to 4.32; TC: OR 1.37, 95% CI 0.77 to 2.43; CC: OR 1 (reference)), and between ischaemic stroke and PDE4D haplotypes at SNP 89–87–83 (A–C–C: OR 2.13, 95% CI 1.15 to 3.96; C–C–T: OR 2.25, 95% CI 1.29 to 3.92), but no association between ischaemic stroke and PDE4D SNP 56, SNP 45 or SNP 41, or with PDE4D haplotypes at SNP 56–45–41. A meta-analysis of nine case–control studies (including our current results) of 3808 stroke cases and 4377 controls confirmed a significant association between stroke and PDE SNP 87 (pooled p = 0.002), SNP 83 (0.003) and SNP 41 (0.003). However, there was statistical heterogeneity (p<0.1) among the studies in the direction of association for each of the individual SNPs tested. Conclusions: Our results and the pooled analyses from all the studies indicate a strong association between PDE4D and ischaemic stroke. This strengthens the evidence that PDE4D plays a key part in the pathogenesis of ischaemic stroke. Heterogeneity among the studies in the direction of association between individual SNPs and stroke suggests that the SNPs tested are in linkage disequilibrium with the causal allele(s).